A review on e-government integration studies - Al-Balushi, Fatma Mohammed (2015)
E-government integration has gained interest of researchers from different perspectives. Some have studied it from organizational perspective; other researchers have proposed models and recommended solutions for technical problems in some government applications. Despite all efforts done, there is no unified definition for e-government integration among scholars. The IS researchers have not done much in e-government do-main. In this article, we set out to progress IS research on e-government integration by recommending a common ground for future research for IS literature. We present a holistic and inclusive definition of e-government integration and discuss the primacy of objectives of undertaking such project so far.